Developing solutions for Microsoft Azure (AZ-204) - Gordon, Adam (Packt Publishing, 2024)
This course takes you on a journey through Azure development, starting with an overview and environment setup, ensuring you have the right tools for success. You'll learn to provision virtual machines, deploy ARM templates, and manage container images with Azure Container Registry. As you advance, you'll create and deploy Azure App Service Web Apps, implement diagnostics logging, and configure web app settings. The course also covers autoscaling rules, ensuring your applications can handle varying loads efficiently. You'll delve into Azure Functions, exploring bindings, triggers, and durable functions, followed by an in-depth look at developing solutions using Cosmos DB and Blob Storage. Security is paramount in cloud solutions, and this course ensures you're well-versed in user authentication, authorization, and secure cloud practices. You'll learn to use the Microsoft Identity Platform, Azure Active Directory, and manage keys, secrets, and certificates. Additionally, the course covers implementing caching with Azure Cache for Redis, troubleshooting solutions using metrics and log data, and managing APIs with Azure API Management. By the end of this course, you'll have the skills and knowledge to develop, deploy, and manage robust, secure, and scalable applications on Azure. What you will learn Set up and configure development environments Provision and manage Azure virtual machines Create and deploy web apps on Azure Implement and manage Azure Functions Develop solutions using Cosmos DB and Blob Storage Secure applications with authentication and authorization Audience This course is designed for software developers, cloud engineers, and IT professionals looking to deepen their Azure development skills. Prerequisites include basic knowledge of cloud computing and familiarity with programming concepts. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Adam Gordon: Adam Gordon has 30+ years as an IT instructor in the private and public sectors. He holds more than 160 IT certifications. He has trained thousands of IT pros over the course of his career. He has over 160 professional and IT certifications.